Using and managing Windows 95 - Adams, Matthew. (John Wiley & Sons, 1997)
This book is about: Introducting Windows 95; Working with Windows 95; Using help; Installing other components; Windows 95 Accessories; File management; Print control; Customising Windows 95; Running multiple applications; ...